Phenolic composition, antioxidant and cytoprotective effects of aqueous‐methanol extract from Anneslea fragrans leaves as affected by drying methods. (24th May 2021) - Cui, Qimin; Wang, Yudan; Zhou, Wenbing; He, Shuyue; Yang, Meilian; Xue, Qingwang; Wang, Yifen; Zhao, Tianrui; Cao, Jianxin; Khan, Afsar; Cheng, Guiguang
Summary: The present study is aimed to evaluate the effect of three different drying methods, including shade drying (SD), freeze drying (FD) and hot air dying (HAD), on the chemical components, antioxidant and cytoprotective activities of aqueous‐methanol extracts from A. fragrans leaves. The total phenolic and flavonoid content were determined by spectroscopic methods, whereas the chemical profile of different extracts was determined by ultra‐high‐performance liquid chromatography coupled with a tandem mass spectrometry (UHPLC‐MS/MS). A total of thirteen compounds were characterised and 9 phenolic compounds have been quantified. Two dihydrochalcone glycosides named confusoside and vacciniifolin were found to be the most abundant phenolic compounds in the SD extract of A. fragrans leaves, which also showed the strongest antioxidant and cytoprotective activities. The results showed that shade drying is an efficient method for preserving the chemical constituents and maintaining the antioxidant and cytoprotective activities of A. fragrans leaves. Abstract : The effect of three different drying methods, including shade drying (SD), freeze drying (FD) and hot air dying (HAD), on the chemical components, antioxidant and cytoprotective activities of aqueous‐methanol extracts from A. fragrans leaves.